Do G-SIBs engage in window-dressing behavior? An empirical analysis - Kamil Pliszka; Carina Schlam (Deutsche Bundesbank, 2025)
This paper examines whether global systemically important banks (G-SIBs) engage in window-dressing behavior to circumvent or reduce regulatory requirements, increasing vul- nerability to economic shocks. Using a comprehensive global bank sample, we uncover ev- idence of such practices: G-SIBs reduce year-end exposures used for G-SIB capital buffer calculations, by roughly twice the magnitude of non-G-SIBs, and reverse these cuts early the next year. This pattern is strongest among G-SIBs that are near bucket thresholds or subject to high G-SIB capital surcharges.
Keywords: G21; G38; 330; Capital Requirements; G-SIB Framework; Systemic Risk; Window Dressing